Effect of Fiber Length on The Composite Properties of Salacca zalacca Pellet Fibers – Epoxy - Andreas; Sinuhaji, Perdinan (Journal of Technomaterial Physics, 2022)
Research on the effect of fiber length on the physical and mechanical properties of composite fibers has been conducted, with variations in fiber lengths of 1 cm, 1.2 cm, 1.4 cm, and 1.6 cm, each added Epoxy and Hardener 1: 1 then stirred by the Hand Lay Up method and pressed for 20 minutes at a temperature of 90ºC. The characterization of composite physical properties showed a density value of 1.1325 g/cm3, porosity by 1.53%, and water absorption by 1.33%. The physical properties of composites have met the standard SNI 03-2105-2006 and can be used as a composite replacement material. The characterization of the composite mechanical properties shows a maximum bending strong value of 25.15 kgf – 40.12 kgf, tensile strength of 11.31 MPa – 15.37 MPa, and a strong impact of 50.43 J/mm2-80.93 J/mm2 has met high impact ABS quality standards of 13.48 J/m2. All mechanical properties of the composite meet the JIS A 5905:2003 standard.